'Opening for business'? Neoliberalism and the cultural politics of modernising planning in Scotland. (April 2018) - Inch, Andy
In this paper I explore how the culture of land-use planning in Scotland has been targeted as an object of modernising reform, exploring how 'culture change' initiatives played a prominent role in stabilising a new settlement around 'open for business' planning between 2006 and 2012, containing potential tensions between diverse goals to make planning more efficient, inclusive and integrative. This highlights the potentially significant role of governance cultures in containing tensions and securing consent to processes of state restructuring. I therefore argue that greater empirical attentiveness to the cultural micro-politics of state restructuring can improve understanding of complex, contemporary dynamics of change, and the contested role of the neoliberal hegemonic project in reshaping urban governance. I conclude by arguing that the continued power of neoliberal critiques of the inefficiency of land-use planning indicate a need to acknowledge and engage contemporary cultural battles over the purposes of planning and urban governance.